الحماية القانونية للمرأة ضد العنف الجنسي في ضوء القانون 19/15 - بن عبيد، سهام (جامعة محمد لمين دباغين سطيف 2, 2018)
أمام تزايد الاعتداءات الجنسية ضد المرأة في الجزائر مع اختلاف صورها كان من اللازم تعزيز الحماية الجنائية، وقد كرس التعديل الأخير لقانون العقوبات القانون 15/19 هذه النظرة من خلال توسيع النطاق التجريمي من جهة، وانتهاج سياسة عقابية صارمة ومشددة لقمع والحد من هذه الجرائم من جهة أخرى. تهدف هذه الدراسة لقياس درجة تطبيق هذه الإجراءات والصعوبات الناجمة عن ذلك في حماية المرأة من الاعتداءات الجنسية.
With the rise of sexual assaults in all their forms against women in Algeria, the strengthening of criminal protection has become more than a necessity. The amendment of the penal code (15/19) has made this vision a reality by widening the criminal context and setting up a highly rigorous repressive policy to punish and put an end to such crimes. The purpose of our study is to evaluate the degree of success of this policy and the difficulties facing women protection against sexual violence
Keywords: التحرش الجنسي -- العنف الجنسي -- الجزائر